2019
DOI: 10.3390/insects10050121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wireless Phosphine Sensors for Monitoring Fumigation Gas in Wheat Stored in Farm Bins

Abstract: Fumigation of grain bins with phosphine tablets is one method of insect control for stored products. Monitoring the concentration of the toxic gas at many locations over several days for a given structure or container can be challenging. In this study, a commercially-available system that wirelessly measures phosphine was evaluated in small-scale and large-scale tests. Small-scale testing was performed to study the repeatability and accuracy of the sensors. The wireless sensors were within 30 ppm of each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, there are cases where phosphine is used for short intervals, as in the case of quarantine and pre-shipment treatments (QPS), in different export scenarios of fruits and vegetables 56,57 . Nevertheless, even in phosphine fumigations that are carried out in large structures, such as silos with grain bulks, the concentration of the gas changes dramatically over time, resulting in large areas to be partially treated, or even untreated [58][59][60] . In a recent study, Agrafioti et al 60 demonstrated that phosphine distribution within silos is rather uneven, and may leave large areas within the grain Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are cases where phosphine is used for short intervals, as in the case of quarantine and pre-shipment treatments (QPS), in different export scenarios of fruits and vegetables 56,57 . Nevertheless, even in phosphine fumigations that are carried out in large structures, such as silos with grain bulks, the concentration of the gas changes dramatically over time, resulting in large areas to be partially treated, or even untreated [58][59][60] . In a recent study, Agrafioti et al 60 demonstrated that phosphine distribution within silos is rather uneven, and may leave large areas within the grain Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Brabec et al 111 designed a wireless gas sensor system for automated detection of PH 3 in order to monitors fumigation treatments, which presents additional information about PH 3 concentration changes during treatments in different areas of grains containers resulted from different events such as effects of weather changes or recirculation fan. According to Figure 3(E), this system included two bines, filled of wheat, and two wireless sensors of PH 3 that were placed at center and wall positions each bine.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…117 So the study of Brabec et al, 111 which applied the wireless gas sensors for automatically evaluation of spaces of grain bines is valuable. As mentioned for study of Brabec et al, 111 the wireless gas sensors were mounted at center and wall locations. As a defect that can be mentioned, the rate of PH 3 release at different regions is different leading to differentiating the saturation rate of wire-less gas sensors at different location.…”
Section: Critical Notementioning
confidence: 99%
See 2 more Smart Citations